Li-rich Unevolved Stars from LAMOST-MRS - Ze-Ming Zhou; Jian-Rong Shi; Shao-Lan Bi; Hong-Liang Yan; Kai-Ke Pan; Ming-Yi Ding; Jiang-Tao Wang; Shuai Liu; Chun-Qian Li; Yu-Tao Zhou; Jing-Hua Zhang; Xiang-Song Fang; et al. (The Astrophysical Journal)
Based on the spectra from the Large Sky Area Multi-Object Fiber Spectroscopic Telescope medium-resolution spectroscopic survey, we select a sample of 88 Li-rich unevolved star candidates. We redetermine their photospheric lithium abundances, A(Li), through the spectral synthesis method, and take the nonlocal thermodynamic equilibrium (NLTE) into account. It is found that there are 62 stars with A(Li) ranging from 3.33 to 4.59 dex. Among them, 23 stars are young stellar objects. There are 33 super Li-rich unevolved stars with A(Li) higher than 3.8 dex, and 24 of them are newly identified. The NLTE corrections for A(Li) are negative, with a maximum value of around 0.5 dex. Our results suggest that the mechanisms such as mass transfer in binary systems, accretion of circumstellar materials, and diffusion processes may contribute to lithium enrichment in their respective samples.